The effectiveness of the implementation of explicit knowledge in quantity surveying firms / Mohammad Ilya Adhwa Abu Bakar and Kartina Alauddin - Abu Bakar, Mohammad Ilya Adhwa; Alauddin, Kartina (2020)
Nowadays, knowledge sharing (KS) and knowledge management (KM) is an essential element to be implemented in an organization. Knowledge has to be managed in order to make it accessible to others within an organization. Most knowledge exists in the minds of an individual until it is encoded into a medium as to enable other people in the organization to understand the information. One of the challenges in retaining knowledge is when an employee leaves an organization for retirement, resignation or for other various reasons. This can affect the effectiveness on the implementation of Explicit Knowledge (EK) in an organization. Hence, it is necessary for knowledge management to be implemented as to being able to retain the knowledge of the coming and going of employees. There are factors that contribute to the effectiveness on the implementation of EK. Thus, the aim of this research is to investigate the factors that contribute to the effectiveness on the implementation of EK in Quantity Surveying firms. Meanwhile, the objectives of this study are to identify the factors that contribute to the effectiveness of the implementation of Explicit Knowledge, to identify the challenges faced by QS in transferring Tacit Knowledge (TK) into Explicit Knowledge and to propose strategies to enhance the implementation of Explicit Knowledge in QS Firms. Unit of analysis in this research is Quantity Surveyors and Assistant Quantity Surveyors available in QS Firms located in Klang Valley. The sampling method used is purposive sampling. This research used the questionnaire survey to collect the primary data. For data analysis, this research using the Statistical Package for the Social Science (SPSS) Version 26.0 where a descriptive analysis is done. Overall, this research found that there are still room for improvements regarding the implementation of EK in QS firms.